Analysis of the Message of Preaching in the Meaning of the Symbols of the SigehPengunten Dance - Agustin, Mae Sella; Muhajir, Muhajir; Kurniawan, Siroy (Jurnal Ilmiah Syi'ar, 2024)
Da'wah does not always have to talk about Islam but the essence of da'wah itself is to convey good things, but it cannot be separated from religious beliefs. The goal to be achieved in this study is to find out the da'wah message contained in the SigehPengunten Dance art. The method in this study is qualitative. The type of library research .This study is descriptive qualitative. Data collection techniques used are documentation, interviews, observations. This study uses the Triangulation data validity technique. The data analysis used is the Miles and Huberman model data analysis where data is collected, reduced, presented and conclusions or verification are drawn. Data processing in this study uses Charles Sanders Peirce's theory analysis.Based on the results of the research conducted by researchers on "Analysis of Preaching Messages in the Meaning of Symbols of the Sigeh Pengunten Dance" is that this dance is a welcoming dance. However, there is a special meaning in several types of SigehPengunten Dance movements related to the message of preaching which is analyzed through the meaning of the symbols of Charles Sanders Peirce's Theory, namely the moral message that can be seen from the LapahTebeng movement which means straight path, Seluang Mudik means returning to the origin, Jong Simpuh Merunduk means respecting guests, Jong Silo Ratu means neat and polite, the Sembah Movement describes the hospitality of the Lampung people , Belah Huwimeans never give up, and Tolak Tebengmeans rejecting evil.